The effect of the Biggs model on the achievement of the literary fifth grade students in the subject of history and the development of the value of patience for them - Ali Al-Jumaili, Mubadder Muhammad; Ali Al- Jubouri, Ahmed Daham (Journal of Tikrit University for Humanities, 2022)
The current research aims to identify (the effect of the Biggs model on the achievement of fifth-grade literary students in the subject of history and the development of the value of patience for them).The researchers adopted the experimental design with two equal groups, to suit the nature of the research, and the research sample consisted of (60) female students who were deliberately selected from the Science High School for Girls. It consisted of (30) female students, who studied the same subject in the traditional way.The researchers identified the educational material to be taught, which included the first and second chapters of the history book for the fifth literary grade to be taught for the academic year (2019-2020) in the Republic of Iraq. , application, analysis, synthesis), and the researchers prepared (12) model teaching plans for both groups.The researchers adopted two tests to measure their research variables. The first test was an achievement test consisting of (40) items (35) objective items of the multiple-choice type with four alternatives, and (5) essay items of the type of short-answer questions, and it verified its validity, stability and distinction. , as well as conducting statistical analyzes of its paragraphs, as the researchers built a measure of the value of patience, which consists of (40) paragraphs, distributed over three areas (the field of patience for obedience, the field of patience for sins, and the field of patience for affliction), for each paragraph three alternatives (a lot, Sometimes, rarely), the validity and reliability of the scale were extracted, and then the discrimination coefficient was calculated for each itemThen the researchers started applying the experiment on and the experiment continued until 9/1/2020 and the results showed that the experimental group outperformed the control group in the achievement test and the measure of patience value.